Stakeholder Perspectives on Barriers for Healthy Living for Low-Income African American Families - Jones, Veronnie Faye; Rowland, Michael L.; Young, Linda; Atwood, Katherine; Thompson, Kirsten; Sterrett, Emma; Honaker, Sarah Morsbach; Williams, Joel E.; Johnson, Knowlton; Davis, Deborah Winders (Frontiers in Pediatrics, 2014)
Background: Childhood obesity is a growing problem for children in the United States, especially for children from low-income, African American families. Objective: The purpose of this qualitative study was to understand facilitators and barriers to engaging in healthy lifestyles faced by low-income African American children and their families. Methods: This qualitative study used semi-structured focus group interviews with eight African American children clinically identified as overweight or obese (BMI > 85) and their parents. An expert panel provided insights in developing culturally appropriate intervention strategies. Results: Child and parent focus group analysis revealed eleven barriers and no definitive facilitators for healthy eating and lifestyles. Parents reported confusion regarding what constitutes nutritional eating, varying needs of family members in terms of issues with weight, and difficulty in engaging the family in appropriate and safe physical activities; to name a few themes. Community experts independently suggested that nutritional information is confusing and, often, contradictory. Additionally, they recommended simple messaging and practical interventions such as helping with shopping lists, meal planning, and identifying simple and inexpensive physical activities. Conclusions: Childhood obesity in the context of low-resource families is a complex problem with no simple solutions. Culturally sensitive and family-informed interventions are needed to support low-income African American families in dealing with childhood obesity.